Effects of functional focus on bounded momentum: Examining firm- and industry-level alliances. (May 2018) - Park, Namgyoo K.; Martin, Xavier; Lee, Jinju; Mezias, John M.
Building on strategic momentum and alliance studies, we theoretically explain and test the non-monotonicity of the alliance momentum of same- or cross-functional-type alliances. We theorize about critical drivers that generate bounded momentum and further argue whether function-specific momentum occurs sequentially or simultaneously. We examine cross-border alliances of 32 international airlines from 1945 to 1994 and find that the inverted U-shaped pattern of alliance momentum holds for same-type but not for cross-type alliances at both the firm and industry levels. These findings imply that alliance momentum with a specific functional focus evolves sequentially rather than simultaneously.